1954
DOI: 10.1111/j.1651-2227.1954.tb15463.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Approach to the Pathogenesis of Retrolental Fibroplasia: I. Changes of the Eye Induced by Exposure of Newborn Mice to Concentrated Oxygen

Abstract: Summary1. Newborn, full‐term mice were subjected to exposures in 98–100 per cent oxygen,(a) intermittently, (b)continuously, or (c)for five days followed by rapid transfer to, and stay in, normal atmosphere. The development of the eyes was followed histologically for 38, 16, and 15 days after birth, respectively.2. Intermittent exposures to oxygen caused a high frequency of persistence, proliferation and dilatation of the retrolental hyaloid vessels with hemorrhages in the primary vitreous body. Eetinal folds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1955
1955
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Rodent models of OIR are widely used, notably because of possible genetic manipulations in mice. Because their retinal vascular development occurs mainly after birth, corresponding to that of a human fetus around 26 weeks gestation [6], rodents have also proved to be useful to study retinal angiogenesis under both normal and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Rodent models of OIR are widely used, notably because of possible genetic manipulations in mice. Because their retinal vascular development occurs mainly after birth, corresponding to that of a human fetus around 26 weeks gestation [6], rodents have also proved to be useful to study retinal angiogenesis under both normal and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…During the 1950's, results gained from the mouse model of oxygen-induced retinopathy [2,3] corroborated findings of the kitten model where it was shown that exposure of newborn kittens to high ambient oxygen could subsequently lead to the production of a proliferative retinopathy [4]. Since then, there has been little new work on the mouse model as an animal model of the proliferative phase of retinopathy of prematurity (ROP) in particular and of the proliferative retinopathies in general.…”
Section: Introductionmentioning
confidence: 56%
“…Patz et al were able to produce what they described as a proliferative retinopathy using 80% inspired oxygen [9] but this interpretation has been disputed [7]. The consensus would appear to be that to produce a proliferative retinopathy in the mouse, the ambient oxygen concentration must be of the order of 98% or so [2,5] such as we used.…”
Section: Discussionmentioning
confidence: 89%
“…Many animal models have been used in the experimental study of oxygeninduced retinopathy (OIR); them most common have been newborn kittens [1][2][3][4], beagle pups [5,6] and newborn mice [7][8][9]. The newborn rat has also been utilized [10,11] and is, in fact, the model we have used in our studies of OIR [12][13][14].…”
Section: Introductionmentioning
confidence: 99%